The Procedure of Enterprise Marketing Diagnostics - Соколова, Л. В.; Верясова, Г. М. (Sp. z o.o. «Nauka i studia», 2011)
The modern economic management conditions that are characterized by environment instability require operative reaction of commodity production enterprises on market conjuncture changes. It stipulates necessity of the regulative enterprise marketing diagnostic procedure implementation. The complex integrated indicator of enterprise marketing diagnostics is suggested in the article as a marketing activity diagnostics index.
Keywords: market; marketing diagnostics; market conjuncture; enterprise; marketing activity diagnostics index